2008
DOI: 10.1128/jcm.02487-07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Xpert Methicillin-Resistant Staphylococcus aureus (MRSA) Assay Using the GeneXpert Real-Time PCR Platform for Rapid Detection of MRSA from Screening Specimens

Abstract: The need for rapid methods to accurately detect methicillin-resistant Staphylococcus aureus (MRSA) is widely acknowledged, and a number of molecular assays are commercially available. This study evaluated the Xpert MRSA assay, which is run on the GeneXpert real-time PCR platform (Cepheid) for use in a clinical laboratory. The following parameters were investigated: (i) the limits of detection (LoDs) for four MRSA strains; (ii) the ability to detect isolates of MRSA from a collection representative of MRSA in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(124 citation statements)
references
References 19 publications
12
110
1
1
Order By: Relevance
“…The LoDs for the Cepheid GeneXpert have been reported for four strains of MRSA collected on Copan swabs and were compared to values for direct and enrichment cultures employing Transwabs with Amies transport medium plated on MRSASelect chromogenic agar and tryptic soy broth (27). The Cepheid GeneXpert detected 610 CFU/ml, corresponding to 58 CFU/swab, compared to 750 CFU/ml and 40 CFU/ml with the direct and enrichment cultures (27). Subsequent studies have reported the LoD for MRSA in the GeneXpert assay to be 109.4 CFU/assay (24) and 3,300 CFU/ml and 250 CFU/swab (26).…”
Section: Discussionmentioning
confidence: 99%
“…The LoDs for the Cepheid GeneXpert have been reported for four strains of MRSA collected on Copan swabs and were compared to values for direct and enrichment cultures employing Transwabs with Amies transport medium plated on MRSASelect chromogenic agar and tryptic soy broth (27). The Cepheid GeneXpert detected 610 CFU/ml, corresponding to 58 CFU/swab, compared to 750 CFU/ml and 40 CFU/ml with the direct and enrichment cultures (27). Subsequent studies have reported the LoD for MRSA in the GeneXpert assay to be 109.4 CFU/assay (24) and 3,300 CFU/ml and 250 CFU/swab (26).…”
Section: Discussionmentioning
confidence: 99%
“…If positive, the specimen is assigned positive screen status. [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] This methodology (called "partial verification") introduces bias in favor of PCR. 115 For MRSA, Yam et al 99 tested 1,246 nares swab specimens with the Lightcycler MRSA Advanced (Roche Molecular Diagnostics, Basel Switzerland), a laboratory developed test (LDT) PCR and, in parallel, cultured all specimens.…”
Section: Shedding Timementioning
confidence: 99%
“…Rossney et al evaluated a commercial platform based on the BD GeneOhm principal for direct detection of MRSA in clinical samples, the GeneXpert MRSA assay (Cepheid Diagnostics, CA, USA) [35]. In this fully automatic, but low-throughput assay, cells are lysed using ultrasonics and DNA from samples is extracted, amplified and detected in separate chambers of single-use disposable cartridges, which contain freeze-dried beads with all reagents required for the real-time process.…”
Section: Genotypic Detection and Identificationmentioning
confidence: 99%